Cultural, Belief, And Lifeway Factors in Diabetes Patients: An Ethnonursing Study - Sumartini Gunawan, Yosephina Elizabeth; Endang Sukartiningsih, Maria Christina; Namuwali, Domianus; Susanto, Tantut (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: The people of Sumba prefer traditional medication from shamans as they believe that diabetes they suffer from the Marapu, hence uncurable by modern medical means. This study aimed to derive a picture regarding diabetes patients’ cultural values, beliefs, and lifeways in the East Sumba ethnic of Indonesia. Methods: This study uses a qualitative design with an ethnographic approach which was conducted in 2018. The main participants in the study were seven diabetic patients, were determined purposively. Focused discussions were held with the person in charge of the non-communicable disease program from seven Public Health Centers. Data were collected from interviews, focus group discussions, field notes and observation sheets. All data were analyzed by content analysis method corresponding to the 4 phases in ethnonursing. Results: Five themes were generated in this study with details of three themes describing the cultural values of diabetic patients (subthemes traditional ceremonies, chewing happa, and traditional medicine), one theme describing the beliefs of diabetic patients (subthemes perceptions about diabetes) and one theme describing the lifestyle of diabetic patients (subthemes eating/drinking patterns, spiritual values, rest/sleep habits, and daily activities). The culture of diabetics depicted in adat ceremonies, happa or betel nut chewing, and traditional medication, which is still thick in East Sumba and their beliefs on the disease they suffer from, exert influence on their daily lives, including their eating or drinking patterns, spiritual values, resting or sleeping patterns, and daily activities. Conclusion: This finding can be helpful for the effort to improve nursing for diabetes patients by cultural approaches.